The Impact of Technology on Economic Development in Somalia - Hilowle, Ibrahim Farah (Multidisciplinary Journal of Horseed International University (MJHIU), 2024)
This study focuses on the impact of technology on economic development in Somalia. The objectives of the study entail: to explore the impact of technology on economic development in Somalia, to analyse the challenges hindering the impact of technology on economic development in Somalia and to determine the necessary strategies to improve the impact of technology on economic development in Somalia. The study employed qualitative research approach and used documentary review to collect data in relation to the impact of technology on economic development in Somalia, the challenges hindering the impact of technology on economic development in Somalia and the necessary strategies to improve the impact of technology on economic development in Somalia. A comprehensive search of academic databases was conducted to identify relevant documentary sources, such as books, research articles, review papers and reports such International Monetary Fund reports, World Bank reports and Federal Government of Somalia reports. The keywords including “technology,” “impact,” “economic development,” “practical challenges” and “practical strategies” were used to retrieve the most pertinent documents. The key findings of the study revealed that technology has got several impact of economic development in Somalia such as improved financial inclusion, increased productivity and income for farmers, improved health of the population, improved education sector and increased job creation. However technology in Somalia is facing several challenges hindering its impact on economic development in Somalia such as limited access to technology, limited access to finance political instability, lack of infrastructure and lack of skilled labor. The necessary strategies to improve the impact of technology on economic development in Somalia entail: investing in improving the country's telecommunications and information technology infrastructure, promoting digital literacy, supporting entrepreneurship, foster collaboration and fostering enabling environment for innovation. The study recommends that Federal Government of Somalia should increase investment in infrastructure, invest in education and skills training, promote entrepreneurship and innovation and support digital financial services to improve the impact of technology on economic development in Somalia.